The augmentative efficacy of second-generation anti-psychotics (SGA) to anti-depressants in treating treatment-resistant depression: a network meta-regression analysis - Binru Bai; Yuwei Li; Xi Chen; Jinsong Huang; Qiaoling Chen; Xinyuan Du; Chengfang Huang; Yi Yang (BMC Psychiatry)
Abstract Background To compare the augmentative efficacy of second-generation anti-psychotics (SGA) to anti-depressants in adult patients with treatment-resistant depression (TRD) adjusting follow-up period and explore the underlying"time window"effects of the regimens. Methods Databases included Embase, PubMed, Scopus, Cochrane Library and Google Scholars as well as Clinicaltrials.gov from inception to May 15, 2024, for relevant randomized controlled studies (RCTs) were retrieved. The primary endpoint was Montgomery Asberg Depression Rating Scale (MADRS). The secondary endpoint was MADRS response rate. The tertiary endpoints were Clinical Global Impression-severity (CGI-S) and MADRS remission rate. Standard mean difference (SMD) and hazard ratio (HR) were generated by Bayesian network meta-regression (NMR) for pairwise comparisons on dichotomous and consecutive variants, respectively. Results A total of 23 studies (N = 10679) with 24 augmentation agents were included in the NMR. For the primary endpoint, compared with ADT, aripiprazole 3 - 12 mg/d, brexpiprazole 1 - 3 mg/d, cariprazine 1.5 - 3 mg/d, olanzapine 6 - 12 mg/d and fluoxetine 25 - 50 mg/d combination, and quetiapine XR were significantly effective (SMD ranged from - 0.28 to - 0.114) and their effect sizes were comparable, after adjusting follow-up period, the results resembled the former except for quetiapine XR (SMD = - 0.10, 95%CI: - 0.212 to 0.014). Brexpiprazole 3 mg/d (7.22 weeks), cariprazine 1 - 2 mg/d (2.97 weeks), cariprazine 2–4.5 mg/d (2.81 weeks), cariprazine 3 mg/d (7.16 weeks), olanzapine 6 - 12 mg/d (4.11 weeks) and quetiapine 150 - 300 mg/d (3.89 weeks) showed"time window". For the secondary endpoint, brexpiprazole 3 mg/d and rispridone 0.5 - 3 mg/d was evidently superior to all others (HR ranged from 1.748 to 2.301). For the tertiary endpoints, as for CGI-S, aripiprazole 2 - 20 mg/d, brexpiprazole 2 - 3 mg/d, cariprazine 3 mg/d, olanzapine 6 - 12 mg/d and fluoxetine 25 - 50 mg/d combination, and rispridone 0.5 - 3 mg/d were conspicuously effective compared with ADT (SMD ranged from - 0.438 to - 0.126) and for MADRS remission rate, aripiprazole 2 - 20 mg/d, brexpiprazole 3 mg/d, cariprazine 3 mg/d, rispridone 0.5 - 3 mg/d were conspicuously effective compared with ADT (HR ranged from 0.477 to 3.326). Conclusion Holistically considering each endpoint and corresponding "time window", certain SGAs appeared to be efficient augmentation to anti-depressants for TRD, but aripiprazole was relatively more effective and better tolerated.